Retention of the Bub3 checkpoint protein on lagging chromosomes - Martinez-Exposito, Maria J. (The National Academy of Sciences, 1999)
Accurate chromosome segregation at mitosis is ensured both by the intrinsic fidelity of the mitotic machinery and by the operation of checkpoints that monitor chromosome-microtubule attachment. When unattached kinetochores are present, anaphase is delayed and the time available for chromosome-microtubule capture increases. Genes required for this delay first were identified in budding yeast (the MAD and BUB genes), but it is not yet known how the checkpoint senses unattached chromosomes or how it signals cell-cycle arrest. We report the isolation and analysis of a murine homologue of BUB3, a gene whose deletion abolishes mitotic checkpoint function in Saccharomyces cerevisiae. mBub3 belongs to a small gene family that has been highly conserved through evolution. By expressing recombinant proteins in insect cells, we show that mBub3, like yeast Bub3p, binds to Bub1 to form a complex with protein kinase activity. During prophase and prometaphase, preceding kinetochore-microtubule attachment, Bub3 localizes to kinetochores. High levels of mBub3 remain associated with lagging chromosomes but not with correctly aligned chromosomes during metaphase, consistent with a role for Bub3 in sensing microtubule attachment. Intriguingly, the number of lagging chromosomes with high Bub3 staining increases dramatically in cells treated with low (and pharmacologically relevant) concentrations of the chemotherapeutic taxol and the microtubule poison nocodazole.